A Standardization Process in its Final Stages: Mine and Thine in A Corpus of English Dialogues 1560–1760 - Kytö, Merja; Walker, Terry (International Journal of English Studies, 2020)
This study concerns the development of the determiners mine/my and thine/thy in the Early Modern English period. The -n forms had essentially been ousted before words starting with consonants over the Middle English period, and over the subsequent centuries, these forms also fell into disuse before words starting with initial vowels and h. While the rise of the n-less variants has been the object of several previous studies, the present investigation aims at accounting for the fate of the declining n-variants in the Corpus of English Dialogues 1560–1760, a data source comprising speech-related texts. We look into the chronological stages of development for the declining mine and thine forms, the genres that maintained these forms longest, and the speaker groups that were the last to use the forms. Comparisons are made with the results obtained in previous studies on mine/my and thine/thy variation.